A Meta-analysis of the Profit-Sharing Practices among Engineering, Construction, and Related Firms: Strategy to Increase Company Revenue - Siman, Bennegreg P. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
This paper explores the impact of profit sharing on employee motivation, productivity, and company performance in the engineering and construction industry. Through a meta-analysis of recent studies, it identifies key factors that influence the effectiveness of profit-sharing programs. The findings reveal that profit sharing significantly boosts employee motivation and productivity, with increases of 15% and 12% respectively. Moreover, job satisfaction rates are 20% higher among employees participating in profit-sharing programs. However, there is a notable preference split, with 60% of employees favoring profit sharing for its potential higher earnings, while 40% prefer fixed salary increases for stability. The research further indicates that frequent and actively managed profit-sharing distributions, such as quarterly payouts, lead to better financial performance, with a 10% increase in overall performance and a 5% improvement in profitability. Project-based profit sharing in the construction sector is particularly effective, resulting in a 25% increase in project completion rates and a 15% reduction in project costs. Additionally, profit sharing is more effective in unionized organizations, with an 18% increase in effectiveness, and mandatory profit-sharing frameworks enhance worker satisfaction and productivity. Based on these findings, the paper recommends developing tailored profit-sharing strategies that cater to different employee preferences, implementing frequent and active management of profit-sharing distributions, adopting project-based profit sharing in project-centric industries, engaging with unions for fair terms, advocating for supportive regulatory frameworks, and continuously monitoring and evaluating the effectiveness of these programs. By adopting these strategies, engineering and construction firms can enhance employee motivation, improve productivity, and achieve better financial performance, driving organizational success.